Recuperação paralela: significações dos(as) alunos(as) do Ensino Médio Integrado ao Técnico Profissional acerca da proposta - Rocha, Andréa Souza Eduardo (2020)
This dissertation has as its theme the proposal of parallel recovery offered to students from Integrated High School to Professional Technicians (EMITP) of the Federal Institute of Education, Science and Technology of São Paulo –Campus Guarulhos (IFSP-GRU). The need to reflect on this issues arose from the professional experience of the researcher as a pedagogue of the IFSP in the Socio-pedagogical Coordination - CSP, added to her experience in the course of schooling. The question that guides this research is: "How do the students from the High School Integrated to the Professional Technician mean the proposal of parallel recovery?". Therefore, the general objective of the study was to investigate what the meanings attributed by these students to the parallel recovery proposal implemented by this institution. The specific objectives were: a) to identify the students' understanding of the proposal; b) apprehend how they feel when participating in the parallel recovery; c) verify possibilities and challenges of the proposal from the perspective of the students. The theoretical framework that underlies this research is mainly composed of the federal legislation on Education; the internal regulations of the Federal Institute that deal with parallel recovery; and reflections by authors who address the theme. This is a qualitative research and tis instruments for collection information are socioeconomic questionnaires and reflective interviews (SZYMANSKI, 2018). For data analysis, we used the meaning nucleous method proposed by Aguiar and Ozella (2006, 2013, 2015), based on Socio-Historical Psychology and which is based on the theoretical assumptions of Karl Marx and Friedrich Engels' Historical-Dialectical Materialism. For the analysis, we built three cores of meaning in order to apprehend the meanings of students about the parallel recovery proposal. Although it is an important and recovering tool for learning, parallel recovery for these students proved to be challenging because of the overhead imposed by the course format and some teaching practices that hinder the learning process